PERBEDAAN PENINGKATAN BERAT BADAN ANTARA AKSEPTOR KB SUNTIK 1 BULAN (CYCLOFEM) DENGAN AKSEPTOR KB SUNTIK 3 BULAN (DEPO MEDROKSI PROGESTERONE ASETAT/DMPA) - Hamimatus matus zainiyah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
ABSTRACT The use of 1-month injectable contraception and 3-month injectable contraception can cause some side effects, such as weight gain. According to research data at BPS Jariyah, 25 people receiving 3-month injections of family planning and 25 people with 1-month injections in September-December 2020. 1-month injection family planning acceptors who experienced weight gain were 16 people and 3 months injection family planning acceptors who experienced weight gain. as many as 18 people. The purpose of this study was to determine the difference in weight gain between 1-month injection family planning acceptors and 3-month injection family planning acceptors. This research uses analytic with cross sectional approach. the independent variable was the difference in weight gain in 1 month injection family planning acceptors and 3 months injection family planning acceptors, dependent on weight gain. The sampling technique is purposive sampling. The data collection instrument used the family planning register book. The population and sample of this study were 1-month injectable family planning acceptors and 3-month injection family planning acceptors with weight gain at BPS Jariyah Amd, Keb Burneh Bangkalan with a population of 56 respondents, a sample of 50 acceptors, purposive sampling technique. This research has been ethically tested by the KEPK STIKes Ngudia Ngudia Husada Madura team. The results showed that most of the respondents who used family planning > 1 year with an increase in body weight were 12 (52.2%). Based on the cross-sectional statistical test, it was obtained that p = 0.036, meaning p = < (0.05, it was concluded that H0 was rejected and Ha was accepted, which means that there was a difference in weight gain between 1 month injectable KB acceptors (Cyclofem) and 3 months injectable KB acceptors ( DMPA). Health workers are expected to be able to provide clear information to 1-month and 3-month injection family planning acceptors regarding side effects that occur to family planning acceptors.